Resistivity Studies On Mn Site Substituted LCMSO Manganites - Bharat R. Kataria; Chirag Savaliya; J. H. Markna (International Journal of Advances in Applied Sciences, 2015)
Effect of Mn-site disorder in La0.67Ca0.33Mn1-xSbxO3 (LCMSO) created by the substitution of Sb5+ at Mn-site is studied through X-ray diffraction (XRD) and temperature dependent resistivity measurements to identify the role of size mismatch at Mn-site and their resistivity property correlations. XRD patterns collected at room temperature for all the LCMSO samples reveal single phasic nature without any detectable impurities within the measurement range studied. XRD data shows that all the samples possess orthorhombic structure without any structural phase transition. Variation in resistivity with Sb5+ content has been discussed in detail in the context of modifications in the structural and magnetic lattices and structural disorder.